Does State-Financed Organic Coffee Certification Increase Smallholder Farmers’ Income? - Hakim, Rizqi Imaduddin; Rifin, Amzul (The Indonesian Forestry Certification Cooperation, 2023)
Many coffee producers in Indonesia carry on organic certification to warrant their production and processing standards. One of them is Nunggal Roso Farmers Group Association (Gapoktan) which performs state-financed organic certification on their robusta coffee products. This research aims to describe farm activities and organic certification applications on Gapoktan Nunggal Roso and analyze its income and profit in 2020. As many as 60 randomly selected respondents consist of 30 organic coffee farmers and 30 non-organic coffee farmers. The organic certification impacts were analyzed using income and profit analysis and then tested for their differences statistically. These research results signify that coffee farms in the research location which has been undertaken in polyculture with shading trees and intercropping plants do not change considerably by the presence of certification. Besides, also known from the research that the return to family labor in each working person-day of organic coffee farmers is lower than that of non-organic coffee farmers.